Crystal Indentation Hardness - Stephen M. Walley (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
Dear Colleagues, Determinations of the indentation hardness properties of crystals have expanded to cover the full characterizations of their important elastic, plastic and cracking behaviors, particularly as accomplished with the increased measuring capabilities of nanoindentation hardness testing. No crystal structure of any bonding type is either too soft or too hard to prevent measurement with a suitable probing indenter. The current Special Issue is devoted to surveying the topic with emphasis given in a collection of reports to: (1) the diversity of crystals being tested; (2) the variety of measuring techniques; and (3) the wealth of information being obtained. Prof. Dr. Ron Armstrong Dr. Stephen Walley Prof. Dr. Wayne L. Elban Guest Editors